Effect of Glycerol, Ethylene Glycol on Morphofunctional Characteristics of Dogs’ Spermatozoa at Different Cryopreservation Stages - Egorov, M. I.; Kopeika, E. F.; Linnik, T. P.; Kuchkov, I. N. (Problems of Cryobiology and Cryomedicine, 2004)
There has been studied the effect of glycerol and ethylene glycol (EG) on survival of dogs’ spermatozoa (DS) after freeze-thawing depending on the concentration of cryoprotectants, cooling regimens and equilibration time, as well as the change in DS cell volume after the cryoprotectants being introduced into suspension by means of turbidimetric method. The highest motility of DS was revealed after cryopreservation under EG protection with final concentration of 7% when being frozen at the first stage with the rate of 3°C/min with no preliminary equilibration. It has been shown that 7% EG causes quite less alterations in cell volume if compared to glycerol.